2021
DOI: 10.3389/fnhum.2021.736155
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Depressed Essential Tremor Using Resting-State Voxel-Wise Global Brain Connectivity: A Multivariate Pattern Analysis

Abstract: Background and Objective: Although depression is one of the most common non-motor symptoms in essential tremor (ET), its pathogenesis and diagnosis biomarker are still unknown. Recently, machine learning multivariate pattern analysis (MVPA) combined with connectivity mapping of resting-state fMRI has provided a promising way to identify patients with depressed ET at the individual level and help to reveal the brain network pathogenesis of depression in patients with ET.Methods: Based on global brain connectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…The default mode network has been generally linked to self-referential processing, affective cognition, and emotion regulation ( 26 ), and disturbances of the default mode network have been confirmed in many neurological and psychiatric disorders including ET ( 27 ). Using voxel-wise global brain connectivity mapping combined with MVPA, a study conducted by our team has shown that the major associated discriminative features in depressed ET were mainly located in the cerebellar-motor-prefrontal cortex circuits ( 12 ). Compared to the previous study, the present study was the first to combine local brain functional connectivity with the MVPA approach to identify depressed ET patients from non-depressed ET and HCs which may help deepen our understanding of the depression pathogenesis of ET from different perspectives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The default mode network has been generally linked to self-referential processing, affective cognition, and emotion regulation ( 26 ), and disturbances of the default mode network have been confirmed in many neurological and psychiatric disorders including ET ( 27 ). Using voxel-wise global brain connectivity mapping combined with MVPA, a study conducted by our team has shown that the major associated discriminative features in depressed ET were mainly located in the cerebellar-motor-prefrontal cortex circuits ( 12 ). Compared to the previous study, the present study was the first to combine local brain functional connectivity with the MVPA approach to identify depressed ET patients from non-depressed ET and HCs which may help deepen our understanding of the depression pathogenesis of ET from different perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to multivariate properties, the MVPA can achieve greater sensitivity for discovering voxel-level subtle and spatially distributed changes of intrinsic brain activity, and are sensitive enough to perform classification at the single-subject level. Combining global brain connectivity of rs-fMRI with MVPA ( 12 ), our latest studies showed good classification performance to identify depressed ET patients. However, whether the MVPA based on local brain connectivity can realize automatic identification of depressed ET has not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a growing number of researchers have used multivariate pattern analysis of neuroimaging data to uncover patterns and assign individual observations to different categories. 36,37 To classify the patients in this study, we employed a multivariate pattern analysis approach noted as SVM. Here, we implement the SVM algorithm under pycharm based on the sklearn library in Python.…”
Section: Participants' Classification With Svmmentioning
confidence: 99%
“…Moreover, ML-combined radiomics has shown to be a promising way to provide quantitative and objective supports for clinical diagnosis and prognosis and help to find a potential target for treatment, such as using ML algorithms based on diagnosis biomarkers from neuroimaging to identify ET from HCs to provide supporting evidence for clinically suspected ET diagnosis and guide the treatment of ET patients. Using ML algorithms combined with voxel-level local connectivity or frequency-dependent intrinsic brain activity analysis, our more recent studies revealed that these ML algorithms could achieve good classification performance to identify ET from healthy controls (HCs) (17)(18)(19). However, up to now, no studies have combined histogram analysis based on ALFF images of Rs-fMRI data with ML algorithms to identify ET patients.…”
Section: Introductionmentioning
confidence: 99%